Exposure to Pb-halide perovskite nanoparticles can deliver bioavailable Pb but does not alter endogenous gut microbiota in zebrafish - Patsiou, Danae (2020)
Lead-halide perovskite nanoparticles (NPs) are a new technology, and investigation of toxicity is of considerable importance due to the potential lead (Pb) release into the environment. The aim of the study was to investigate aqueous and dietary toxicity of Pb-halide perovskite NP and Pb in zebrafish Danio rerio. Perovskite NP toxicity was evaluated in zebrafish by mortality, gene expression, histopathology, and phylogenetic analysis of gut microbiota. Zebrafish larvae were exposed to five Pb-halide perovskite NPs in parallel with Pb(NO3)2 exposures, and zebrafish adults were exposed to the three perovskite NPs that caused the strongest effect and Pb(NO3)2. No median lethal concentration (LC50) was observed for zebrafish larvae exposed to up to 200 mg/L of perovskite NPs for 96 h. Mortality, metallothionein 2 (mt2) and δ-aminolevulinic acid dehydratase (ala-d) gene expression (24-h exposure) in zebrafish larvae after aqueous perovskite NPs exposures did not differ from total Pb concentration - response curves. The lack of differences in mortality and gene expression between perovskite NPs and soluble Pb after aqueous exposure suggest that toxicity from perovskite NPs can be attributed to bioavailable Pb rather than nano-specific effects. Induction of mt2 and reduction of ala-d expression levels in liver tissues showed Pb bioavailability after 2-d and 4-d dietary exposure to perovskite-spiked feeds. Changes in gut microbiota of adult zebrafish were detected after 14-d exposure to Pb-spiked food, but no changes were detected from perovskite-NP spiked food. The phylogenetic analysis identified different microbiome profiles of Pb-fed fish compared to perovskite-fed fish suggesting a different mechanism of toxicity. Exposure to Pb-halide perovskite NPs led to absorption of Pb likely from release of Pb ions rather than absorption of NPs. Pb-halide perovskite NPs can release bioavailable Pb and this needs to be considered during the development of this technology.